Muslim-friendly facilities in the hospitality industry: offering facilities in accordance with religious tenets - Ramli, Noriah (TM-Info-Media Sdn. Bhd., 2009)
The idea of creating Muslimfriendly hotels or Shariah compliant hospitality is nothing new. The concept of Islamic Hotel Brand or Muslim-Friendly Hotelier to accommodate Muslims need is not any different then the current western hotels' hospitality. A room having a Qiblah pointing signage stuck on the ceiling, a prayer rug or sajadah, a bidet or an arch stretching somewhere in the room is considered authentically within the Islamic culture.